Please play safe! Penguin's guide to playground safety - Cuyler, Margery; Hillenbrand, Will. (New York Scholastic Press, 2006)
Penguin and his animal friends demonstrate how to play safely and use good manners.
Keywords: Safety -- Fiction; Etiquette -- Fiction; Behavior -- Fiction; Animals -- Fiction